2002
DOI: 10.1152/ajpheart.00224.2002
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and strain distribution of the C57BL/6 mouse aorta

Abstract: The goal of the present study was to obtain a systematic set of data along the length of the mouse aorta to study variations of morphometry (diameter, wall thickness, and curvature), strain, and stress of the mouse aorta. Five mice were imaged with a 13-MHz ultrasound probe to determine the in vivo diameter along the aorta. A cast was made of these aortas to validate the ultrasonic diameter measurements. The root mean squared and systematic errors for these measurements were 12.6% and 6.4% of the mean ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
43
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 21 publications
12
43
1
Order By: Relevance
“…IVSR varies with location in the vascular tree (28,30) and age (84). Our data confirm that locational differences exist in newborn Fbln4 ϩ/ϩ mice and are consistent with previous observations.…”
Section: Discussionsupporting
confidence: 93%
“…IVSR varies with location in the vascular tree (28,30) and age (84). Our data confirm that locational differences exist in newborn Fbln4 ϩ/ϩ mice and are consistent with previous observations.…”
Section: Discussionsupporting
confidence: 93%
“…Figure 9A shows the model-predicted ratio of the in situ axial length of the aorta to the unloaded excised length (1/Λ u ) when the assumed axial stretch ratio of the elastin due to arterial growth ( ) is varied from 1.1 to 2.0 along the length of the aorta. These results agree well with the experimental data of Guo et al (2002), which are also shown.…”
Section: Effects Of Axial Stretchsupporting
confidence: 92%
“…Guo et al (2002), for example, have reproduced many of the experiments done by Liu and Fung, but in C57bl/6 mice. They found variations in the opening angle along the aorta, but the variations they found were quite different from those of Liu and Fung (1988).…”
Section: Implications Of This Studymentioning
confidence: 52%
See 1 more Smart Citation
“…Future studies will attempt to Large asymmetric bifurcations show a predilection for atherosclerosis. Such bifurcations have been extensively studied biologically (2,4,11,12,16,26). Here, we include the loss coefficients to consider the loss of energy at a bifurcation in the 1-D model.…”
Section: Discussionmentioning
confidence: 99%